The Responses of Ionospheric Conductivities on the Mid-Latitudes to Changes in the BZ Component of Interplanetary Magnetic Field - Timocin, Erdinc; Yesil, Ali; Unal, Ibrahim (Springer, 2020)
In this study, we investigate the response of the ionospheric conductivities on the middle latitudes to the southward and northward turnings of the B-Z component of the interplanetary magnetic field (IMF). For this purpose, parallel conductivity (sigma(0)), Pedersen conductivity (sigma(1)), Hall conductivity (sigma(2)) data calculated for Rome (41.8 degrees N, 12.5 degrees E); Juliusruh (54.6 degrees N, 13.4 degrees E); Uppsala (59.8 degrees N, 17.6 degrees E); Lycksele (64.7 degrees N, 18.8 degrees E) during the 22nd solar cycle are examined. The superposed epoch analysis method is used to investigate the response of the conductivities to the southward and northward turnings of the B-Z component. From the analysis results it is observed that the turnings in the B-Z component of the IMF have significant effect on all conductivities. At the event moment (zero time), the southward turnings of the B-Z component increases all conductivities while the northward turnings of the B-Z component decreases all conductivities. The effect on the conductivities of the changes in the B-Z component occurs before about 18 h from the event moment, and this effect disappears after about 24 h from the event moment. Furthermore, all of ionospheric conductivities shows or does less reaction to changes in the B-Z component as latitude increase.
Keywords: Ionosphere; Ionospheric conductivities; Interplanetary magnetic field; Superposed epoch analysis